Comparison of melanoma gene expression score with histopathology, fluorescence in situ hybridization, and SNP array for the classification of melanocytic neoplasms. (November 2018) - Reimann, Julie; Salim, Sadia; Velazquez, Elsa; Wang, Lu; Williams, Kelly; Flejter, Wendy; Brooke, Linda; Sunder, Sujatha; Busam, Klaus
Abstract While most melanomas can be distinguished from nevi by histopathology, the histology is ambiguous for some melanocytic tumors, contributing to diagnostic uncertainty. Therefore molecular assays, including FISH or SNP array, and more recently a gene expression test (myPath, Myriad Genetics) have been proposed to aid in the work-up of ambiguous tumors. Two hundred and sixty-eight prospectively submitted cases were gathered, with the goal of comparing the myPath assay to morphologic diagnosis in (1) morphologically unequivocal cases (198), and to morphologic diagnosis and FISH in (2) morphologically ambiguous cases (70). Melanoma FISH was performed using probes for 6p25, 6q23, 11q13, Cep6, 9p21, and Cep9 and scored according to established criteria. The myPath assay was scored by the manufacturer as benign, indeterminate, or malignant. In the unequivocal group, myPath assay showed 75% agreement with morphologic diagnosis, with 67% sensitivity and 81% specificity. In the ambiguous group, FISH and myPath showed 69% inter-test agreement. For these cases agreement with histopathologic interpretation was 84% for FISH and 74% for myPath. Sensitivity and specificity of FISH was 61 and 100%, 50 and 93% for myPath, respectively. Cases from both groups in which myPath was discordant with either morphologic diagnosis and/or FISH (81/268 cases), were submitted for evaluation by two experienced dermatopathologist and also by SNP-array. SNP-array results correlated better than FISH, which correlated better than myPath, with the morphologic interpretation. Our findings document that molecular diagnostics show good correlation with consensus diagnoses, but discordant results occur, and vary in level of correlation with consensus interpretations. Studies with long-term outcomes data within specific ambiguous lesion subsets are required to establish the accuracy of this test, as each molecular diagnostic technique has limitations based on both lack of clinical outcomes data in ambiguous melanocytic tumors and in terms of their sensitivity and specificity in melanocytic lesion subtypes.